2013
DOI: 10.1371/journal.pone.0072484
|View full text |Cite
|
Sign up to set email alerts
|

Authorship Bias in Violence Risk Assessment? A Systematic Review and Meta-Analysis

Abstract: Various financial and non-financial conflicts of interests have been shown to influence the reporting of research findings, particularly in clinical medicine. In this study, we examine whether this extends to prognostic instruments designed to assess violence risk. Such instruments have increasingly become a routine part of clinical practice in mental health and criminal justice settings. The present meta-analysis investigated whether an authorship effect exists in the violence risk assessment literature by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 37 publications
2
55
0
2
Order By: Relevance
“…When these studies were eliminated, publication year was no longer correlated with the effect size and had no effect in the multiple regression analysis. Interestingly, the fact that authors who design a given test find higher validity estimates than those reported in subsequent studies has been shown before, not only for psychophysiological deception detection tests (Krapohl, ), but also for prognostic instruments designed to assess violence risk (Singh, Grann, & Fazel, ).…”
Section: Discussionmentioning
confidence: 79%
“…When these studies were eliminated, publication year was no longer correlated with the effect size and had no effect in the multiple regression analysis. Interestingly, the fact that authors who design a given test find higher validity estimates than those reported in subsequent studies has been shown before, not only for psychophysiological deception detection tests (Krapohl, ), but also for prognostic instruments designed to assess violence risk (Singh, Grann, & Fazel, ).…”
Section: Discussionmentioning
confidence: 79%
“…From a purely empirical standpoint, it is widely accepted that (a) a risk assessment should be structured and informed by empirically supported risk cues (Dawson, 2000;Elbogen et al, 2010), and (b) actuarial approaches are superior to unstructured clinical judgment in terms of predicting recidivism (Grove et al, 2000;Hanson & Morton-Bourgon, 2009). Nonetheless, recent work has called into question whether the evidence supports the sole use of actuarial tools in the prediction of recidivism risk (Fazel et al, 2012;Singh et al, 2013). Furthermore, team-based models that encompass shared assessments of patient risk and strive to establish agreement across multiple providers have been shown to reduce the unreliability of clinical judgment and improve predictive accuracy of recidivism outcomes (Campbell, 1995;Elbogen, 2002).…”
Section: Summary and Implications For Risk Assessment With Jivsmentioning
confidence: 99%
“…In replication studies, existing risk instruments can identify groups of high-risk patients who are approximately three times more likely to be violent than low-risk patients (15). In replication studies, existing risk instruments can identify groups of high-risk patients who are approximately three times more likely to be violent than low-risk patients (15).…”
Section: Treatment Of Psychosis and Risk Assessment For Violencementioning
confidence: 99%